Effects of internal rural-urban migration on rural non-farm enterprises: Evidence from Thailand and Vietnam - Katharina Grabrucker (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2021)
Migration is a phenomenon of increasing global relevance as year by year a growing number of individuals is leaving their home driven by the pursuit to improve the well-being of their households through additional income. While the drivers of international migration and its effect on the left-behind households have been well researched, less focus has been put on the effects of internal, rural-urban migration (and its concomitant remittances). This paper analyses the net effects of remittances from internal, rural-urban migrants on selfemployment and on investments of the left-behind households by using a rich household level panel data set from Thailand and Vietnam. The findings indicate that individuals from households receiving remittances from internal, rural-urban migrants are less likely to be self-employed - both in Thailand and Vietnam. The channels through which remittances affect the labor supply of the receiving households cannot be determined with certainty, yet one of the potential reasons might be that left-behind household members need to compensate for the lost labor of the migrant who was previously engaged in farm activities. Moreover, the results show for some specifications lower investments of migrant households into farm and non-farm assets, while the expenditure on consumption is higher compared to households without migrants. This might be an indication that non-farm activities are less important for rural left-behind households, while remittances might be directly used to increase the consumption level - which might have been low before the migration.
Keywords: D22; F24; O15; Q12; R23; 330; Internal migration; Remittances; Rural non-farm enterprises; Thailand; Vietnam